Inlfuence Orange Juice Consuming In Increasing Hemoglobin Levels In Teenage Girls At SMK Negeri 3 Medan In 2021 - Debby Pratiwi; Marlina Marlina (Institute of Computer Science (IOCS), 2022)
The World Health Organization (WHO) in 2016 stated that about a third of the world's population (32.9%) was estimated to suffer from anemia. The population groups most vulnerable to anemia are children under five (42%) especially infants and children under the age of 2 years, adolescents (39%), and pregnant women (46%). This study aims to determine the effect of orange juice consumption on increasing hemoglobin levels in adolescent girls at SMK Negeri 3 Medan in 2021. This study is a quantitative study with an Analytical Experiment (Quasy Experiment) research design with a Randomized Pretest and Posttest with Control Group Design. The population in this study were young women aged 13-16 years, at SMK Negeri 3 Medan in 2021. The results showed the average hemoglobin level of the pre-test experimental group (10.14 g/dL), and the post-test results of the experimental group (10.51 g/dL) with a difference (0.37 g/dL). While the average pre-test hemoglobin level in the control group was (9.94 g/dL) with post-test results (9.86 g/dL) and the difference (-0.8 g/dL). Based on the Shapiro Wilk test, the A-Symp Sig value was 0.005 <.05. It can be concluded that the consumption of orange juice has an effect on increasing hemoglobin levels in adolescent girls at SMK Negeri 3 Medan in 2021. It is hoped that the results of this study can be an alternative non-pharmacological treatment of anemia.